Skinnytaste. High protein : 100 healthy, simple recipes to fuel your day - Homolka, Gina; Jones, Heather K. (Clarkson Potter/Publishers, 2025)
"Gina Homolka, founder of the longstanding go-to healthy eating blog Skinnytaste, is an expert at creating super simple, weeknight friendly, flavor-packed recipes that meet all your dietary needs, and in Skinnytaste High Protein, she delivers on that promise with 100 high-protein meals. Whether you're looking for creative ways to incorporate more protein into your diet, go-to recipes to jazz up your favorite proteins, or ideas for nutritionally balanced meals that will keep you satiated, Gina has you covered. Each recipe packs at least thirty grams of protein per serving (including options for vegetarian, dairy-free, and gluten-free eaters) and there are plenty of one-pot, meal-prep friendly, and streamlined recipes for every meal of the day. Start your day with a Mango-Blueberry Smoothie or Chicken Chorizo Breakfast Tacos. Turn hearty proteins into a complete meal with Grilled Chicken Thighs and Charred Corn Summer Salad, Sheet Pan Chili-Lime Salmon Fish Tacos, and Seared Steaks with Dijon-Mushroom Sauce and Roasted Asparagus. Gina also offers protein-boosted versions of classics like A Monte Cristo Omelet Sandwich or Peanut Butter and Jammy Crepes. And if you need a midday protein boost, prep a DIY Spicy Salmon Roll or Chilled Shrimp Salad with Eggs. With nutritional information included for each recipe and recipes labeled for gluten-free and dairy-free ingredients, Skinnytaste High Protein will be your go-to resource for nutritious meals that pack a protein punch"-- Provided by publisher.